A Review of contemporary sewage sludge treatment and management methods in European countries with an emphasis on Greece - Eleftheriadou, Aikaterini; Akratos, Christos; Vavatsikos, Athanasios; Gratziou, Maria Evridiki (Technical Annals, 2023)
Municipal sewage sludge is an acute problem in both developed and developing countries. Researchers are conducting many experiments to solve this problem. There are many methods of disposal, neutralization, or reuse of sediments after neutralization. The review of contemporary sewage sludge treatment and management methods in European countries with an emphasis on Greece will provide more information about the most appropriate choice for the use of sewage sludge in Greece. The difficulties associated with adapting sewage sludge management to the requirements of sustainable development are discussed. The article draws information from the publication of Official Gazette 2692/B/21-04-2023 as well as the projects currently implemented in Greece regarding the treatment of sludge in Urban Wastewater Treatment Units. The forecasts and directions of processing sewage sludge in Greece are also investigated, through the inspection of the commitments and forecasts of the National Waste Management Plan 2015, compared to the new/ updated National Waste Management Plan of 2020. In Greece after the introduction of the project "Treatment and purification of urban wastewater in environmentally sensitive settlements and modernization of facilities" of the Recovery and Resilience Fund from 17/01/2023, there is a growing trend towards thermal treatment of sludge using drying methods (solar etc. etc.) which by 2025 will have reformed the facts of the disposal of treated sludge in Greece. However, the examination of the issue of managing the sludge produced by municipal urban waste treatment units and the choice of the appropriate strategy for the management of urban sewage sludge remains a complex problem.